From Silent to Authoritarian Revolution: Modi, Hindu Rashtra and the Paradox of Indian Democracy - KAZUYA NAKAMIZO (The Journal of Indian and Asian Studies)
India is currently undergoing an authoritarian revolution. During the 10 years of Narendra Modi’s rule, liberal aspects of India’s democracy were attacked by malpractices and the institutionalization of illiberal laws under his government. Additionally, the freedom of the media has been seriously damaged by the arrests of journalists who have criticized Modi’s government, which was, in particular, enabled by the amendment of the Unlawful Activities (Prevention) Act (UAPA) in 2019. The nation-wide anti-Citizenship Amendment Act (CAA) was crushed by the sudden declaration of the All-India Lockdown under the guise of an anti-COVID-19 measure, which I have termed the practice of “Disaster Authoritarianism”. After the crackdown on the anti-CAA movement, its participants were arrested under the provisions of a renewed UAPA. These are representative examples of Modi’s authoritarian revolution. Before this authoritarian revolution, India had been a democratic country for 70 years, a rarity among the countries of the so-called Global South. Why and how is this authoritarian revolution happening? Indian democracy underwent democratization that empowered the lower sections of society in the 1990s in what has been called the “Silent Revolution”. I hypothesize that this “Silent Revolution” invited Modi’s Authoritarian Revolution, which would constitute the paradox of Indian democracy. In this article, I seek to analyze the political process that led to the current Authoritarian Revolution and how it could occur without formal regime change.